Prenatal cocaine exposure: The role of cumulative environmental risk and maternal harshness in the development of child internalizing behavior problems in Kindergarten - Eiden, Rina D. (2014)
This study examined the associations between prenatal exposure to cocaine and other substances and child internalizing behavior problems at Kindergarten. We investigated whether maternal harshness or cumulative environmental risk mediated or moderated this association. Participants consisted of 216 (116 cocaine exposed, 100 non-cocaine exposed) mother-infant dyads participating in an ongoing longitudinal study of prenatal cocaine exposure. Results indicated that, as hypothesized, maternal harshness moderated the association between prenatal cocaine exposure to child internalizing in Kindergarten such that prenatal cocaine exposure increased risk for internalizing problems at high levels of maternal harshness from 7 to 36 months and decreased risk at low levels of harshness. Contrary to hypothesis, the association between prenatal cocaine exposure and child internalizing in Kindergarten was not mediated by maternal harshness or cumulative environmental risk. However, cumulative environmental risk (from 1 month of child age to Kindergarten) was predictive of child internalizing behavior problems at Kindergarten. Results have implications for parenting interventions that may be targeted toward reducing maternal harshness in high risk samples characterized by maternal substance use in pregnancy.